The Oracle: A Sam and Remi Fargo Adventure - Cussler, Clive; Burcell, Robin; Brick, Scott ([New York, NY] : Penguin Audio, 2019)
Searching for a cache of cursed scrolls from sixth-century northern Africa, treasure hunters Sam and Remi Fargo confront rival crime bands that have taken students hostage to steal supply shipments from a charity-funded Nigerian school.
"The husband-and-wife treasure-hunting team of Sam and Remi Fargo return in a new adventure as they search for an ancient scroll--which carries a deadly curse--in this thrilling addition to Clive Cussler's bestselling series. In 533 A.D., the last Vandal ruler in North Africa consults an oracle on how to defeat the invading Byzantine army. The oracle tells the king that a high priestess cast a curse upon the Vandal Kingdom after a sacred scroll was stolen. In order to lift the curse, the scroll must be returned to its rightful home. But the kingdom falls before the scroll is found, leaving its location a great mystery. until a current day archaeological dig, funded by Sam and Remi Fargo, uncovers some vital clues. The search for the ancient scroll is put on hold when the Fargos learn that a shipment of supplies intended for their charitable foundation's school has been stolen, and they travel to Nigeria to deliver new supplies themselves. But their mission becomes infinitely more complicated when they run afoul of a band of robbers. The group takes Remi and several students hostage, and there are signs that the kidnapping is related to the missing scroll. The Fargos need all their skills to save the lives of the young girls at the school before they uncover the hidden treasure. and lift the deadly curse"--
Keywords: Fargo, Sam -- (Fictitious character) -- Fiction; Fargo, Remi -- (Fictitious character) -- Fiction; Fargo, Remi -- (Fictitious character); Fargo, Sam -- (Fictitious character); Scrolls -- Fiction; Blessing and cursing. -- Fiction; Antiquities -- Fiction; Antiquities; Blessing and cursing; Scrolls; Nigeria -- Fiction; Nigeria; Action and adventure fiction; Audiobooks; Fiction; Thrillers (Fiction); Action and adventure fiction; Thrillers (Fiction); Fiction; Audiobooks